Exploring community reintegration among Nigerian stroke survivors - Michael O. Ogunlana; Olufemi O. Oyewole; Abiola Fafolahan; Pragashnie Govender (AOSIS, 2023)
Background: Community reintegration is one of the ultimate goals of stroke rehabilitation. The increasing burden of stroke morbidity by other non-communicable diseases in Nigeria indicated the need for our study. Objectives: The authors explored the factors contributing to successful community reintegration among Nigerian stroke survivors. Method: We conducted an explorative qualitative study design to achieve this aim using in-depth semi-structured interviews with 12-purposively sampled stroke survivors. Results: Three overarching themes emerged: restriction of participation experienced by stroke survivors, activity limitation as pointers to the quality-of-life experience of stroke survivors and enablers or barriers to community reintegration for stroke survivors. Among the core, sub-themes included incapability of returning to work, difficulty performing domestic activities, social isolation or separation, recreation and leisure time. Enablers of community reintegration included creating a positive mindset, encouragement and social support, while barriers included mobility and speech or language challenges. Conclusion: Stroke survivors have challenges in returning to work and experience varying levels of activity limitation, which affects their quality of life with identifiable enablers or barriers to community reintegration. Clinical implications: Stroke survivors with severe functional deficits should be monitored closely and given further rehabilitative assistance to aid functional recovery, thereby facilitating community reintegration.